Thermodynamic model of the coupled valence and spin state transition in cobaltates. (11th December 2020) - Hardy, V; Bréard, Y; Guillou, F
Abstract: A class of cobalt-based oxides exhibits a peculiar type of transition, entangling valence and spin state degrees of freedom of 4f and 3d elements. It constitutes one of the most spectacular illustrations of the interplay between charge, spin and lattice degrees of freedom in strongly correlated materials. In this work, we present a thermodynamic model capable to reproduce the main features of this transition. Our approach is based on the minimization of a free energy combining the contributions of two sublattices and the interaction between them. The coupling energies introduced in the model are related to well-known chemical pressure effects in the perovskite structure. The results of this model are compared to experimental data derived from x-ray absorption spectroscopy.